2021
DOI: 10.1016/j.aip.2021.101839
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 and absence of music therapy: Impact on mother-child dyad during invasive procedures in pediatric oncology

Abstract: During COVID-19 pandemic, Italian pediatric oncology departments were obliged to adopt restrictive measures to minimize the risk of in-hospital infections in frail patients and staff members. Access to the wards was significantly reduced and music therapy (MT) activities were suspended. The aim of this study was to compare the level of anxiety and sedation in pediatric patients undergoing invasive procedure before (T1), during(T2) and after(T3) the pandemic, with and without the presence of MT. From… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Consistent with social referencing and emotional contagion research, pediatric cancer studies indicate a strong positive relationship between parent and child distress, with young children most vulnerable to parent distress 8,26–29 . Given the strength of this relationship, use of a family‐based, dyadic approach is well justified, yet rarely seen in pediatric oncology intervention trials 30 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Consistent with social referencing and emotional contagion research, pediatric cancer studies indicate a strong positive relationship between parent and child distress, with young children most vulnerable to parent distress 8,26–29 . Given the strength of this relationship, use of a family‐based, dyadic approach is well justified, yet rarely seen in pediatric oncology intervention trials 30 .…”
Section: Discussionmentioning
confidence: 97%
“…The morale I guess is what you call it, it totally brings it up" (F4-4B). Another parent noted "I think just being able to play, being able to not think about cancer for 15, 20 minutes, and just be 5 (years old)" Consistent with social referencing and emotional contagion research, pediatric cancer studies indicate a strong positive relationship between parent and child distress, with young children most vulnerable to parent distress 8,[26][27][28][29]. Given the strength of this relationship, TA B L E 3 Themes, subthemes, and representative quotes.…”
mentioning
confidence: 85%
“…MT can be considered an excellent support for anesthesia as a complementary/non-pharmacological approach to reduce pre-operative anxiety in children undergoing invasive procedure [6,17].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from Cochrane systematic reviews shows that MT can decrease anxiety in patients with cancer [19], coronary heart diseases [20] and in patients on mechanical ventilation [9]. Some studies have reported that music interventions reduce sedative requirements in patients undergoing regional anesthesia when combined with sedation, using both midazolam [21,22] and propofol, and also in critically ill patients in intensive care units [9,13].…”
Section: Introductionmentioning
confidence: 99%